Prevalence of hypertension amongst spouses in urban area of Nagpur city, Maharashtra, India - Deshpande, Amit V.; Chaudhary, Sanjeev M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Students of human biology share an interest in studies of family clusters of heart disease and its antecedents. The recent inclusion of husband and wife pairs (spouse pairs) has added a new dimension to earlier studies of first degree relatives. Blood pressure is influenced by environmental factors operating within genetic limits. Since married couples share a similar environment, the study can identify environmental factors. This study was done to find out prevalence and control of hypertension among spouses in urban area of Nagpur. Methods: This was a community based cross sectional study conducted in urban area of Nagpur city. 260 couples in whom both husband and wife were of age 30 or more were included. Blood pressure was measured and classified as per WHO guidelines. Results: Prevalence of hypertension was found to be 51.9% among husbands and 40.8% among wives. 57.8% husbands and 50.9% wives were unaware of their hypertensive status. Among those who were aware, 35.1% husbands and 15.4% wives had their blood pressure. Conclusions: The observation suggests need for targeting married couples as a unit of intervention for hypertension awareness and control. This study also emphasizes the need to increase the knowledge of current guidelines for detection and treatment of hypertension among physicians.